A cross-sectional study on the effect of physical disability on self-esteem among adolescents in Kabale municipality. - Ndamira , Nickolas; Bahati, Ronald; Otwine, Anne (Student’s Journal of Health Research Africa, 2025)
Introduction Physical disability significantly affects adolescents’ self-esteem, especially in low-resource settings. Globally, adolescents with disabilities experience social exclusion, stigma, and limited access to education and healthcare, negatively influencing their psychological well-being. This study examined the effect of physical disability on self-esteem among adolescents in Kabale Municipality. The objectives were to: (1) determine forms of physical disability, (2) assess levels of self-esteem, (3) evaluate the relationship between disability and self-esteem, and (4) establish the effect of disability on daily functioning. Methods A cross-sectional, quantitative design was employed, using standardized tools, including the Rosenberg Self-Esteem Scale and the Barthel Index, to assess self-esteem and daily functioning. A total of 94 adolescents with physical disabilities, aged 13–18 years, were selected through a snowball sampling approach. Data were gathered using structured questionnaires translated into Rukiga and analyzed with descriptive and inferential statistics, including ANOVA and Tukey’s HSD test, to examine associations between disability type and self-esteem. Results Amputations (45.7%) and paralysis (33%) were the most common disabilities. A majority (80.9%) of respondents exhibited low self-esteem, with mean scores differing by disability: monocular vision (12.45), paralysis (11.67), amputations (10.23), and congenital amputations (9.56). ANOVA confirmed a significant relationship between disability type and self-esteem (F = 4.76, p = 0.004). Post-hoc analysis indicated adolescents with monocular vision had significantly higher self-esteem compared to amputees (p = 0.012) and congenital amputees (p = 0.008). Daily functioning was severely limited, with 60.6% needing major assistance for mobility and 24.5% immobile, impairments strongly linked to lower self-esteem. Conclusion Physical disability negatively impacts self-esteem and daily functioning among adolescents in Kabale Municipality, with amputations and paralysis exerting the greatest effects. Recommendations Targeted psychosocial interventions, improved access to mobility aids, and inclusive education policies to enhance independence. Further research should investigate longitudinal outcomes and localized strategies for adolescent well-being.